Gayatri Chakravorty Spivak - Morton, Stephen (Routledge, 2007)
Gayatri Chakravorty Spivak offers an overtly political challenge to the way we think about literature and culture. As she highlights the many legacies of colonialism, she re-defines the ethical horizons of contemporary critical thought. This volume focuses on her key theoretical concepts, intellectual context and critical reception, providing an accessible introduction to one of the most important thinkers of our time. Stephen Morton introduces Spivak's crucial work through an analysis of such issues as: * methodology and Spivak's 'difficult' style * deconstructive strategies * third world women, the concept of the 'subaltern' and the critique of western feminism * re-reading Marx for the global capitalist era * Spivak's contribution to colonial discourse studies and postcolonial theory. Having examined the ways in which Spivak has transformed contemporary cultural theory, and in particular feminist and postcolonial thought, Morton concludes with a guide to reading Spivak's work and that of her critics. Essential for students of literature or cultural studies, this volume is the ideal companion for a first encounter with Spivak's remarkable texts.